Large size growth of terbium doped BaCl2/NaCl/KCl eutectic for radiation imaging. (8th February 2022) - Takizawa, Yui; Kamada, Kei; Kim, Kyoung Jin; Yoshino, Masao; Yamaji, Akihiro; Kurosawa, Shunsuke; Yokota, Yuui; Sato, Hiroki; Toyoda, Satoshi; Ohashi, Yuji; Hanada, Takashi; Kochurikhin, Vladimir. V.; et al.
Abstract: In this study, a large-size eutectic scintillator of Tb-doped BaCl2 /NaCl/KCl was grown using the Czochralski (Cz) and halide vertical Bridgman methods (H-VB). The suitability of these two growth methods for growing the eutectic was compared. Finally, 1 inch diameter eutectic bulks were obtained using the H-VB method. The Tb 3+ -derived strongest intensity peak at approximately 550 nm was observed by X-ray irradiation. An approximately 3 × 3 mm transparent eutectic wafer was cut and polished from the grown eutectic bulk. An imaging test using α -ray was performed using the grown eutectic, a fiber optic plate, and an electron-multiplying CCD camera. The resolution performance for radiation-imaging applications was evaluated.